Salmonella bacteria in farm animal feeds. Review - N. B. Shadrova; O. V. Pruntova; G. S. Skitovich; О. А. Akulich (Ветеринария сегодня)
This review provides a data analysis of the test results for farm animal feeds. The analysis is based on the articles published from 1955 to 2020. It was found that the overall pooled prevalence estimates of Salmonella was 0.14: with a prevalence of 0.18 in raw feed components, 0.09 – in finished feed and 0.08 – in swabs from the surfaces of feed production equipment. The probability of contaminating raw animal feed components with Salmonella is 3.9 times higher than that for raw vegetable feeds. There is a tendency for Salmonella to be less detected in raw feed components; however, in finished feeds Salmonella detectability has remained unchanged for decades. The Salmonella prevalence in samples taken from environmental objects and surfaces of feed mill production equipment was 0.08. The risk of Salmonella detection at feed mills in the pre-heat treatment zone was 1.5 times higher than the risk of detection in the post-heat treatment zone. The analysis of Salmonella serovariants revealed that S. senftenberg, S. montevideo, S. typhimurium, S. anatum, S. havana, S. enteritidis, S. cerro are isolated everywhere. The S. salford serotype is found only on the African continent. A research into antimicrobial resistance of Salmonella isolates demonstrated resistance to such medicinalproducts as ceftriaxone, carbopenem and imipenem; and full genome sequencing showed at least one antibiotic resistance gene in 40% of Salmonella isolates detected at pig feed production plants.